2004
DOI: 10.1063/1.1766076
|View full text |Cite
|
Sign up to set email alerts
|

Nanopillar growth mode by vapor-liquid-solid epitaxy

Abstract: We report epitaxial growth of Ge nanopillars (NPs) on Si(100) by vapor-liquid-solid (VLS) growth from digermane. This growth morphology is characterized by short, low-aspect-ratio pillars and is markedly different from the long, narrow nanowires (NWs) previously reported for VLS growth. The NP growth mode occurs at low digermane pressures. It is attributed to surface-diffusion-induced lateral growth in combination with an insufficient Ge concentration gradient in the AuGe eutectic to catalyze NW growth. High r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This rectifying behavior is consistent with that observed at bulk Au/Ge interfaces [34], where a large Schottky barrier of 0.59 eV is present, and is nearly independent of the type of metal due to strong Fermi level pinning close to the Ge valence band. Our observations are also consistent with atom-probe tomography measurements [33] and with high-resolution transmission electron microscopy which indicated an abrupt interface between the Au-catalyst nanoparticle and the Ge nanowires [35]. Fig.…”
Section: Au Catalyst-ge Nanowire Schottky Diodessupporting
confidence: 90%
“…This rectifying behavior is consistent with that observed at bulk Au/Ge interfaces [34], where a large Schottky barrier of 0.59 eV is present, and is nearly independent of the type of metal due to strong Fermi level pinning close to the Ge valence band. Our observations are also consistent with atom-probe tomography measurements [33] and with high-resolution transmission electron microscopy which indicated an abrupt interface between the Au-catalyst nanoparticle and the Ge nanowires [35]. Fig.…”
Section: Au Catalyst-ge Nanowire Schottky Diodessupporting
confidence: 90%
“…This rectifying behavior is consistent with that observed at bulk Au/Ge interfaces [11], where a large Schottky barrier of 0.59 eV is present, and is essentially independent of the type of metal because Ge has strong Fermi level pinning close to the valence band. Our observations are also consistent with atom-probe tomography measurements [12] and with high-resolution transmission electron microscopy [13] which indicated an abrupt interface between the Au catalyst nanoparticle and the Ge nanowires. It is tempting to analyze the rectifying behavior using conventional thermionic emission theory to extract the Schottky barrier.…”
supporting
confidence: 89%
“…For nanowires grown axially at atmospheric pressure, it has been suggested that hydrogen termination from the pyrolysis of hydride precursors may block the adsorption site of the vapour [29] and promote nanowire growth. When the precursor was reduced at lower pressure, the hydrogen termination effect decreased, so the lateral growth led to the porous [30] or pillar [31] structure formation.…”
Section: Nanostructures Deposited On Nanopatterned Featuresmentioning
confidence: 99%